Example.1
Prove that + +
+ -------- + = .
Solution
LHS = +
+ +
-------- +
++ 2
+ -------- + n
= n + (n–1) + (n–2)
+ …. …..(1).
= = RHS
Example.2
Find the sum of the series
Solution
The given series
Now, =
Similarly, etc.
Hence, the gives
series =
= =
Example.3
If ,
prove that for n ≥ 2, .
Solution
For x ∈ R, we have
….
(1)
We know that ax2
+ 2bx + c ≥ 0 for each x ∈ R if b2 –ac £ 0
and a > 0.
Since 2n –1 >
0, The inequality in (1) will hold if and only if
Example.4
If (1 +x)n
= C0 + C1x + C2x2 +.. . . . +Cnxn.
Find .
(a)
(b)
Solution
(a) We have
&⇒
Differentiating both
the sides we get
Putting x = 1 in the
above expression, we get
…(1)
But
= …(2)
Let us now evaluate
We have (1+x)n
= C0+C1x+C2x2 + …+Cnxn …(3)
Differentiating both
sides w.r.t.x we get.
&⇒ …(4)
Replacing x by 1/x
in (3) we get
…(5)
Note that = coefficient of constant term
in
[using (4) and (5)]
= coefficient of
constant term in
= coefficient of xn-1
in (1+x)n [n(1+x)n-1]
= coefficient of xn-1
in n (1+x)2n-1 = n. (2n-1Cn-1).
Thus, from (2) we
get
=
&⇒
&⇒
(b) We have
=
Since
=
&⇒ 2
= n
= = 2
&⇒ =
\
= + 2
Example.5
Show that nC0 –nC1+nC2+ . . . .
Solution
We
have
=
+ . . . (1)
We know that
Differentiating both sides w.r.t y, we get.
-
Thus
= . . . .(2)
and -
= - .
. . . (3)
Putting these values in (1), we obtain
= =